2020
DOI: 10.1126/sciadv.aax6346
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation and IL-1 signaling during placental malaria induce poor pregnancy outcomes

Abstract: Placental malaria (PM) is associated with severe inflammation leading to abortion, preterm delivery, and intrauterine growth restriction. Innate immunity responses play critical roles, but the mechanisms underlying placental immunopathology are still unclear. Here, we investigated the role of inflammasome activation in PM by scrutinizing human placenta samples from an endemic area and ablating inflammasome components in a PM mouse model. The reduction in birth weight in babies from infected mothers is parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…Activation of NLRP3 and AIM2 inflammasomes, together with high expression of IL-1R, IL-1β, and caspase-1 was recently shown in the placental tissue of mothers infected with P. falciparum with significant pathology (107). In a murine model of intra-amniotic inflammation induced by bacterial LPS, tissue sections from the decidua basalis region expressed high levels of NLRP3, but negligible caspase-1 activation suggesting a possible non-canonical activation of the NLRP3 inflammasome (108).…”
Section: Cytosolic Pattern Recognition Receptors: Rig-i Mda5 and Nomentioning
confidence: 93%
“…Activation of NLRP3 and AIM2 inflammasomes, together with high expression of IL-1R, IL-1β, and caspase-1 was recently shown in the placental tissue of mothers infected with P. falciparum with significant pathology (107). In a murine model of intra-amniotic inflammation induced by bacterial LPS, tissue sections from the decidua basalis region expressed high levels of NLRP3, but negligible caspase-1 activation suggesting a possible non-canonical activation of the NLRP3 inflammasome (108).…”
Section: Cytosolic Pattern Recognition Receptors: Rig-i Mda5 and Nomentioning
confidence: 93%
“…Prominent inflammatory infiltration by monocytes/macrophages causing massive chronic intervillositis is related to severe placental malaria [18]. Inflammatory response to placental malaria inhibits mTOR signaling which is key [19]. Intervillositis due to placental malaria was found to be associated with increased autophagosome formation but decreased autophagosome/ lysosome fusion leading to autophagosome accumulation in syncytiotrophoblasts blocking placental amino acid uptake [20•].…”
Section: Introductionmentioning
confidence: 99%
“…Also, blockage of mTOR signaling due to placental malaria leads to decreased placental amino acid uptake [ 20 •]. Recently, it was found that placental malaria stimulates placental expression of inflammasomes which are linked to placental secretion and maturation of IL-1β, a pro-inflammatory cytokine that causes diminished nutrient transporter expression [ 19 ]. Thus, during placental malaria, the usually anti-inflammatory placental environment evolves into a pro-inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that inhibition of NF-κB inflammatory signaling exerts neuroprotective functions in BE rat models ( 9 ). IL-1β ( 11 , 12 ) and TGF-β ( 13 - 15 ) are two common cytokines secreted by immune cells; they were found to be upregulated in many immune diseases ( 11 , 15 ); however, their expression patterns, as well as their clinical significance in BE, have not been discussed thus far. In the current study, we found that both IL-1β and TGF-β expression levels were markedly increased in the serum of BE patients compared with those of healthy controls.…”
Section: Discussionmentioning
confidence: 99%